PTU-033 Meta-Analysis of Flexible Spectral Imaging Colour Enhancement (Fice) in Detection and Characterization of Colorectal Polyps. (4th June 2013) - Raychaudhuri, C; Mohammed, N; Subramanian, V
Abstract : Introduction: Several endoscopic innovations have been developed recently to improve detection and characterization of colorectal polyps. Flexible spectral imaging colour enhancement (FICE) is a form of image enhanced endoscopy which enhances the visualisation of mucosal structures and microcirculation by the selection of spectral transmission with a dedicated wavelength. Methods: Various electronic databases were searched for articles reporting on detection and characterization of colonic polyps comparing standard while light endoscopy and FICE. The pooled mean differences in total numbers of polyps, adenomatous polyps, flat adenomas, and hyperplastic polyps detected was calculated. Additionally, pooled sensitivity, specificity, positive and negative likelihood ratio, diagnostic odds ratio and pooled area under the receiver operating curve was calculated. A fixed effects model was used unless there was significant heterogeneity. Publication bias was assessed using Funnel plots and Egger's test and heterogeneity was assessed using Cochran's Q and the I2 test. Results: 5 studies/2150 patients and 11 studies/2425 patients were included in the analysis for detection of polyps and polyp characterization respectively. There were no differences between FICE and standard colonoscopy for the detection of all polyps, adenomatous polyps, flat adenoma or hyperplastic polyps (Table 1). Table 2 lists the pooled diagnostic accuracy parameters for FICE. A random effects model was used in both because there was heterogeneity between the studies. Conclusion: FICE does not seem to improve the detection rate of adenomatous polyps during screening colonoscopy. These results may partially be due to the small number of studies done so far using FICE. The pooled sensitivity and specificity of FICE does not meet the currently accepted criteria of the ASGE PIVI committee for use in routine clinical practise. Disclosure of Interest: None Declared